Method for detecting molecular weight of polylactic acid after aging based on fluorescence lifetime change of fluorescent probe

CN122983007APending Publication Date: 2026-10-27XINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611358815.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明提供了一种基于荧光探针的荧光寿命变化检测聚乳酸老化后分子量的方法,克服了上述现有技术之不足,其能有效解决现有聚乳酸材料老化检测手段破坏性强、前处理繁琐、荧光强度法信号干扰大、定量精度不足的问题

Benefits of technology

[0018]本发明利用四苯乙烯基聚集诱导发光荧光探针的荧光寿命对聚乳酸基体微观环境高度敏感的特性实现聚乳酸老化后分子量的检测;聚乳酸老化降解后荧光寿命随之缩短;且荧光寿命与聚乳酸重均分子量的对数值呈稳定线性关系,据此建立定量关联模型,即可通过无损检测荧光寿命快速、精准地判定聚乳酸材料的老化后的分子量;探针可预先复合于材料内部,无需破坏性取样,同一样品可连续跟踪老化全过程;适配薄膜、纤维、注塑件等多种制品形态及水解、热氧、紫外等多种老化模式,可灵敏区分不同批次产品的耐老化性能差异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present application relates to the technical field of polymer material aging, and is a method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime change of fluorescent probe, which comprises the following steps: a tetraphenyl ethylene-based aggregation-induced emission fluorescent probe is compounded with polylactic acid to prepare a polylactic acid sample to be tested loaded with the fluorescent probe; after aging treatment of the sample, a time-correlated single photon counting method is used to collect a fluorescence decay curve and fit to obtain an average fluorescence lifetime; and the fluorescence lifetime is substituted into a quantitative correlation model of fluorescence lifetime and weight average molecular weight of polylactic acid to calculate the weight average molecular weight of polylactic acid after aging. The present application takes fluorescence lifetime as a detection index, and the signal is stable and not interfered by light source fluctuation, sample thickness and light bleaching, so that quantitative detection of the molecular weight of polylactic acid after aging can be realized in a nondestructive, in-situ and rapid manner, the relative deviation of quantitative prediction is less than 5%, the aging degree of polylactic acid is reflected, and the present application is suitable for aging evaluation and batch quality screening of various polylactic acid products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer material aging technology, and is a method for detecting the molecular weight of polylactic acid after aging based on the fluorescence lifetime change of a fluorescent probe. Background Technology

[0002] Polylactic acid (PLA) is a fully biodegradable polymer material widely used in food packaging, medical consumables, textile fibers, 3D printing, and other fields. However, PLA is highly susceptible to molecular chain hydrolysis and thermo-oxidative breakage under humid, hot, ultraviolet, oxygen, and high-temperature environments. This leads to continuous changes in the matrix's micro-viscosity and free volume, resulting in a gradual decline and failure of the material's mechanical and barrier properties. Therefore, accurate quantitative assessment of the aging degree of PLA products is a core aspect of material life prediction and service safety assessment.

[0003] Currently, commonly used methods for characterizing the aging of polylactic acid (PLA) in the industry include gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and mechanical tensile testing. These methods have significant drawbacks: GPC and mechanical testing are destructive tests, and samples cannot be reused; infrared and thermal analysis have low sensitivity, only capable of characterizing macroscopic performance changes in the later stages of aging; all detection methods require complex sample pretreatment, resulting in long testing cycles and making it difficult to achieve rapid, in-situ screening in batches.

[0004] Fluorescent probe technology, as a highly sensitive analytical method, has been widely used in fields such as bioimaging, environmental monitoring, and materials science. In recent years, fluorescent probe technology has been introduced into the field of polymer aging monitoring. For example, existing technologies have reported monitoring polymer degradation processes by doping fluorescent probes and observing changes in fluorescence emission intensity (MA C, GUO Q, MO J, et al. Monitoring and kinetic study of alkaline hydrolysis of polylactic acid fibrous membrane via aggregation-induced emission (AIE) technique [J / OL]. Surfaces and Interfaces, 2023, 42: 103433. DOI: 10.1016 / j.surfin.2023.103433). However, the fluorescence intensity signal is proportional to the number of probe molecules and is easily affected by external factors such as excitation power drift, sample thickness differences, and photobleaching effects, resulting in unreliable quantitative results. There are also reports of using fluorescent probes to post-dye label polymer aging sites (LI Y, TIAN R, WANG P, et al. Fluorescence monitoring of the degradation evolution of aliphatic polyesters[J / OL]. Chemical Communications, 2022, 58(63):8818-8821.DOI:10.1039 / D2CC02150A.), and performing two-dimensional and three-dimensional fluorescence imaging using laser scanning confocal microscopy to analyze the degree of aging using geometric parameters such as aging area, depth, and volume. However, the above-mentioned existing methods all use fluorescence intensity or fluorescence imaging geometric parameters as the detection basis, and fail to utilize the more robust photophysical parameter of fluorescence lifetime.

[0005] Fluorescence lifetime is the average residence time of fluorescent molecules in excited states, determined by both radiative and non-radiative transition rates. The non-radiative transition rate is highly sensitive to the microenvironment of the polymer matrix; moreover, fluorescence lifetime values ​​are unaffected by excitation light intensity, sample thickness, or photobleaching, exhibiting signal stability far superior to fluorescence intensity. Currently, there are no patents or literature reports on the quantitative correlation between fluorescence lifetime and the molecular weight of polylactic acid (PLA), making it impossible to achieve non-destructive and rapid determination of the molecular weight of PLA after aging. Summary of the Invention

[0006] This invention provides a method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using fluorescent probes. This method overcomes the shortcomings of the prior art and effectively solves the problems of existing polylactic acid material aging detection methods being highly destructive, having cumbersome pretreatment, and suffering from significant signal interference and insufficient quantitative accuracy in fluorescence intensity methods.

[0007] The technical solution of this invention is achieved through the following measures: a method for detecting the molecular weight of polylactic acid after aging based on the fluorescence lifetime change of a fluorescent probe, comprising the following steps: Step 1: Composite the fluorescent probe with a polylactic acid substrate to obtain a polylactic acid sample uniformly loaded with the fluorescent probe. Step 2: Aging treatment is performed on the polylactic acid sample to be tested; Step 3: Collect the fluorescence decay curve of the fluorescent probe in the aged polylactic acid test sample to obtain the fluorescence lifetime; Step 4: Substitute the fluorescence lifetime of the aged polylactic acid (PLA) test sample into the pre-established quantitative correlation model between fluorescence lifetime and PLA weight-average molecular weight to calculate the weight-average molecular weight of the aged PLA test sample.

[0008] The following are further optimizations and / or improvements to one of the above-mentioned inventive technical solutions: The aforementioned fluorescent probe is a tetraphenylethylene-based aggregation-induced emission fluorescent probe, which comprises a tetraphenylethylene fluorescent core and oligolactic acid segments covalently grafted onto the tetraphenylethylene fluorescent core.

[0009] The mass ratio of the fluorescent probe to the polylactic acid substrate is from 0.25:99.75 to 1:99.

[0010] The above-mentioned composite method is one of physical doping, covalent bonding, or core-shell structure embedding.

[0011] The above-mentioned tetraphenylethylene-based aggregation-induced emission fluorescent probe was melt-blended with polylactic acid at a temperature of 175°C to 185°C.

[0012] The above-mentioned aging treatment is one of hydrolytic aging, thermo-oxidative aging, ultraviolet aging, or natural environmental aging.

[0013] The above aging treatment is a hydrolytic aging treatment, which is carried out in an aqueous solution with a pH value of 4 to 10.

[0014] In step three above, the fluorescence decay curve of the fluorescent probe in the aged polylactic acid test sample is collected, including: Fluorescence decay curves were acquired using time-correlated single-photon counting with pulsed laser as the excitation source at wavelengths of 320 nm to 340 nm and fluorescence acquisition wavelengths of 450 nm to 470 nm.

[0015] In step three above, the average fluorescence lifetime is the intensity-weighted average fluorescence lifetime, obtained by fitting the fluorescence decay curve using a double exponential function. The calculation formula is as follows: In the formula: t A1 represents the intensity-weighted average fluorescence lifetime (in ns); A2 and A1 are the pre-exponential factors for short-lived and long-lived fluorescent components, respectively. t 1. t 2 represents the fluorescence lifetimes of the short-lifetime and long-lifetime components, respectively.

[0016] Step four above establishes a quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight, including: Multiple sets of polylactic acid standard samples loaded with fluorescent probes were prepared and subjected to aging treatment for different durations to obtain multiple sets of aged polylactic acid standard samples. The average fluorescence lifetime of polylactic acid standard samples after aging treatment was determined. The weight-average molecular weight of polylactic acid standard samples after aging treatment in each group was determined by gel permeation chromatography. A quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight was established by linear fitting with the logarithm of weight-average molecular weight as the ordinate and the average fluorescence lifetime as the abscissa. The expression for the quantitative correlation model between the fluorescence lifetime and the weight-average molecular weight of polylactic acid is as follows: in, Weight-average molecular weight (unit: g / mol). t The fluorescence lifetime value is expressed in nanoseconds (ns). a and b This is a constant related to the aging path.

[0017] The above-mentioned tetraphenylethylene-based aggregation-induced emission fluorescent probe was prepared according to the following method: Aminotetraphenylene and L-lactide undergo a polymerization reaction under the action of a catalyst. The reaction product is purified and dried to obtain a tetraphenylethylene-based aggregation-induced emission fluorescent probe. The molar ratio of aminotetraphenylene to L-lactide is 1:1000; The catalyst is stannous octoate; The polymerization reaction is carried out under inert gas protection at a temperature of 110°C to 130°C for 10 to 15 hours.

[0018] This invention utilizes the highly sensitive fluorescence lifetime of a tetraphenylethylene-based aggregation-induced emission fluorescent probe to the microenvironment of the polylactic acid (PLA) matrix to detect the molecular weight of PLA after aging. The fluorescence lifetime shortens as PLA ages and degrades, and a stable linear relationship is established between the fluorescence lifetime and the logarithm of the PLA's weight-average molecular weight. Based on this, a quantitative correlation model can be established, allowing for rapid and accurate determination of the molecular weight of aged PLA materials through non-destructive fluorescence lifetime testing. The probe can be pre-assembled into the material, eliminating the need for destructive sampling, and the entire aging process can be continuously tracked for the same sample. It is adaptable to various product forms such as films, fibers, and injection molded parts, and various aging modes such as hydrolysis, thermo-oxidation, and ultraviolet light, and can sensitively distinguish the differences in aging resistance between different batches of products. Detailed Implementation

[0019] This invention is not limited to the following embodiments, and specific implementation methods can be determined according to the technical solutions and actual conditions of this invention. Unless otherwise specified, all chemical reagents and chemicals mentioned in this invention are well-known and commonly used chemical reagents and chemicals in the prior art; unless otherwise specified, all percentages in this invention are mass percentages; unless otherwise specified, all solutions in this invention are aqueous solutions with water as the solvent, for example, hydrochloric acid solution is an aqueous solution of hydrochloric acid; room temperature in this invention generally refers to a temperature between 15°C and 25°C, generally defined as 25°C.

[0020] The present invention will be further described below with reference to embodiments: Example 1: The method for detecting the molecular weight of polylactic acid after aging based on the fluorescence lifetime change of a fluorescent probe includes the following steps: Step 1: Composite the fluorescent probe with a polylactic acid substrate to obtain a polylactic acid sample uniformly loaded with the fluorescent probe. Step 2: Aging treatment is performed on the polylactic acid sample to be tested; Step 3: Collect the fluorescence decay curve of the fluorescent probe in the aged polylactic acid test sample to obtain the fluorescence lifetime; Step 4: Substitute the fluorescence lifetime of the aged polylactic acid (PLA) test sample into the pre-established quantitative correlation model between fluorescence lifetime and PLA weight-average molecular weight to calculate the weight-average molecular weight of the aged PLA test sample.

[0021] Example 2: As an optimization of the above example, the fluorescent probe is a tetraphenylethylene-based aggregation-induced emission fluorescent probe, which comprises a tetraphenylethylene fluorescent core and oligolactic acid segments covalently grafted onto the tetraphenylethylene fluorescent core.

[0022] Example 3: As an optimization of the above examples, the mass ratio of fluorescent probe to polylactic acid substrate is 0.25:99.75 to 1:99.

[0023] Example 4: As an optimization of the above examples, the composite method is one of physical doping, covalent bonding, or core-shell structure embedding.

[0024] Example 5: As an optimization of the above example, a tetraphenylethylene-based aggregation-induced emission fluorescent probe and polylactic acid were melt-blended and composited at a temperature of 175°C to 185°C.

[0025] Example 6: As an optimization of the above examples, the aging treatment is one of hydrolytic aging, thermo-oxidative aging, ultraviolet aging, or natural environmental aging.

[0026] Example 7: As an optimization of the above examples, the aging treatment is a hydrolytic aging treatment, which is carried out in an aqueous solution with a pH of 4 to 10.

[0027] Example 8: As an optimization of the above examples, in step three, the fluorescence decay curve of the fluorescent probe in the aged polylactic acid test sample is collected, including: Fluorescence decay curves were acquired using time-correlated single-photon counting, with pulsed laser as the excitation source. The excitation wavelength ranged from 320 nm to 340 nm, and the fluorescence acquisition wavelength ranged from 450 nm to 470 nm.

[0028] Example 9: As an optimization of the above examples, in step three, the average fluorescence lifetime is the intensity-weighted average fluorescence lifetime, obtained by fitting the fluorescence decay curve using a double exponential function. The calculation formula is as follows: In the formula: t A1 represents the intensity-weighted average fluorescence lifetime (in ns); A2 and A1 are the pre-exponential factors for short-lived and long-lived fluorescent components, respectively. t 1. t 2 represents the fluorescence lifetimes of the short-lifetime and long-lifetime components, respectively.

[0029] Example 10: As an optimization of the above examples, step four involves establishing a quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight, including: Multiple sets of polylactic acid standard samples loaded with fluorescent probes were prepared and subjected to aging treatment for different durations to obtain multiple sets of aged polylactic acid standard samples. The average fluorescence lifetime of polylactic acid standard samples after aging treatment was determined. The weight-average molecular weight of polylactic acid standard samples after aging treatment in each group was determined by gel permeation chromatography. A quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight was established by linear fitting with the logarithm of weight-average molecular weight as the ordinate and the average fluorescence lifetime as the abscissa. Example 11: As an optimization of the above examples, the expression for the quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight is as follows: in, Weight-average molecular weight (unit: g / mol). t The fluorescence lifetime value is expressed in nanoseconds (ns). a and b This is a constant related to the aging path.

[0030] Example 12: As an optimization of the above examples, a tetraphenylethylene-based aggregation-induced emission fluorescent probe was prepared according to the following method: Aminotetraphenylene and L-lactide undergo a polymerization reaction under the action of a catalyst. The reaction product is purified and dried to obtain a tetraphenylethylene-based aggregation-induced emission fluorescent probe. The molar ratio of aminotetraphenylene to L-lactide is 1:1000; The catalyst is stannous octoate; The polymerization reaction is carried out under inert gas protection at a temperature of 110°C to 130°C for 10 to 15 hours.

[0031] Example 13: In this embodiment, the raw material used has a weight-average molecular weight of 1.0 × 10⁻⁶. 5 g / mol polylactic acid masterbatch was used as a standard sample for polylactic acid.

[0032] (1) Synthesis of tetraphenylethylene-based aggregation-induced emission fluorescent probe Aminotetraphenylene (0.3 mmol) and graft monomer L-lactide (0.3 mol) were added at a molar ratio of 1:1000, and stannous octoate (0.6 mmol) was added as a catalyst. The reaction was carried out under nitrogen protection at 120 °C with stirring for 12 hours. After cooling, the crude product was dissolved in dichloromethane, purified three times by precipitation with ice-cold methanol, and dried under vacuum at 45 °C to obtain a white powder of tetraphenylethylene-based aggregation-induced emission fluorescent probe with a yield of 85%. The probe was verified to have aggregation-induced emission effect by using a tetrahydrofuran / water mixed solvent.

[0033] (2) Preparation of PLA thin film Polylactic acid standard samples were thoroughly mixed with 0.75% by mass of tetraphenylethylene-based aggregation-induced emission fluorescent probes and fed into a single-screw blown film extruder with segmented temperatures of 175℃, 180℃, and 185℃. Standard sample films with thicknesses of 30μm to 40μm were prepared by controlling the blow-up ratio of 2.5:1. Two parallel samples were prepared for each aging time gradient and used for fluorescence lifetime testing and GPC molecular weight calibration, respectively.

[0034] (3) Neutral environment gradient hydrolysis aging treatment Using deionized water with pH=7 as the aging medium, the solid-liquid ratio of the standard sample film to the aqueous solution was 1g:10mL. All samples were sealed and placed in a constant temperature water bath at 25℃, protected from light. Eight aging gradients were set for 0 days, 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, and 49 days. After reaching the set time, the film was removed, rinsed three times with deionized water, dried with nitrogen, and cooled to room temperature in the dark before testing.

[0035] (4) Sample fluorescence lifetime detection Each standard sample film was analyzed in triplicate, and fluorescence decay curves were collected. Short- and long-lived component parameters were obtained by fitting a bi-exponential model, and then a weighted average formula was used. Fluorescence lifetime was calculated, and the arithmetic mean of the three detection results was taken as the final data. The results are shown in Table 1.

[0036] In this embodiment, the fitting results for the unaged sample are τ1=2.31ns, τ2=5.62ns, A1=0.41, A2=0.59, and the calculated average fluorescence lifetime is τ=4.53ns.

[0037] The fitting results for samples neutrally aged for 49 days were τ1=2.84ns, τ2=4.42ns, A1=0.74, A2=0.26, and τ=3.40ns. It can be seen that the fluorescence lifetime continuously decreases with increasing aging time.

[0038] Multiple parallel tests were conducted on standard sample films with aging times of 0 days, 14 days, 28 days, and 49 days. The results are shown in Table 2. The relative standard deviations of the six parallel test results were all less than or equal to 0.14%, indicating that the fluorescence lifetime detection has good stability and repeatability.

[0039] (5) Construct a quantitative model of fluorescence lifetime and aging degree Standard sample films used for calibration at various aging time points were cut into small pieces, dissolved in tetrahydrofuran, and their weight-average molecular weight was determined by GPC and its logarithm was calculated. A linear fitting was performed with fluorescence lifetime as the independent variable and the logarithm of molecular weight as the dependent variable to obtain a quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight in a neutral hydrolysis system. The model has a linear correlation coefficient R² = 0.9691, indicating excellent linear correlation.

[0040] (6) Quantitative detection of aging samples The polylactic acid sample to be tested was subjected to steps (2) to (4). The average fluorescence lifetime was obtained by three parallel tests, and the weight-average molecular weight after aging of the sample from 0 to 49 days was calculated. The results are shown in Table 3.

[0041] (7) Method accuracy verification Parallel samples of the test sample were subjected to GPC destructive testing, and the results are shown in Table 4. The relative deviations between the calculated predicted values ​​and the measured values ​​were all less than 5%, proving that the prediction accuracy of the quantitative model meets the requirements of industrial quantitative testing, and the quantitative results of the testing method are reliable.

[0042] Example 14: Using deionized water with pH=4 and pH=10 as aging media, respectively, 1.0×10 5 Perform the operations as described in steps (2) to (5) of Example 13 using g / mol polylactic acid masterbatch.

[0043] The quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight under pH=4 hydrolysis conditions is as follows: The correlation coefficient R² = 0.9489; The quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight under pH=10 hydrolysis conditions is as follows: The correlation coefficient R² = 0.9706; The linear correlation coefficients were all greater than 0.94, indicating good linear correlation. This means that under acidic and alkaline hydrolysis aging environments, the fluorescence lifetime of the fluorescent probe and the weight-average molecular weight of polylactic acid have a stable and reliable linear relationship. This detection method is not limited to neutral water environment and can be adapted to different pH hydrolysis aging conditions. Only the corresponding quantitative model for each aging path needs to be changed to complete the non-destructive quantitative detection of the degree of aging of polylactic acid. The method has a wide range of applications.

[0044] Example 15: Three batches from different manufacturers (A, B, and C) were selected, with an initial molecular weight of 1.0 × 10⁻⁶. 5 For polylactic acid products of g / mol, the fluorescence lifetimes of the three groups of samples were obtained after aging for 7 days, 14 days and 21 days, respectively, following steps (2) to (4) in Example 14. The weight-average molecular weight of the samples after aging was calculated, and the results are shown in Table 5 below.

[0045] This embodiment selects products from three different manufacturers, all with a molecular weight of 1.0 × 10⁻⁶. 5Polylactic acid (PLA) granules (g / mol) were introduced with fluorescent probes and prepared into samples. These samples were aged for different times under the same neutral hydrolysis conditions, and the fluorescence lifetime (τ) was measured. The predicted molecular weight was calculated using a quantitative correlation model between fluorescence lifetime and PLA weight-average molecular weight. Under the same aging conditions, the fluorescence lifetime decay rates of the three groups of film samples differed significantly. Films from manufacturer A had higher predicted molecular weights than those from manufacturers B and C, and exhibited the smallest fluorescence lifetime decrease. Films from manufacturer C had the lowest predicted molecular weight and the fastest fluorescence lifetime decay. Films from manufacturer B were in the middle range. It can be predicted that PLA products from manufacturer A have the best hydrolytic aging resistance, followed by films from manufacturer B, and the worst films from manufacturer C. Therefore, products from manufacturer A have the longest expected service life and the best quality under the same service conditions. This method does not require destructive sampling; it can quickly quantify the differences in aging resistance between different manufacturers simply by measuring fluorescence lifetime, providing a reliable basis for product screening and quality control.

[0046] The fluorescent probe used in this invention is based on the intramolecular motion restriction mechanism, and its fluorescence lifetime τ = 1 / (kᵣ + k n ᵣ). Aging leads to the breakage of polylactic acid molecular chains, an increase in free volume, and a decrease in microviscosity. This weakens the restriction on intramolecular motion of the probe molecules and reduces the nonradiative transition rate k. n As the free volume (ᵣ) increases, the fluorescence lifetime decreases. Therefore, changes in fluorescence lifetime directly reflect the degree of change in the matrix's free volume and molecular weight. Different batches of products exhibit varying hydrolysis chain-scission rates and different kinetics of free volume increase due to differences in polymerization processes, residual catalysts, and initial crystallinity. This ultimately manifests as differences in the rate of fluorescence lifetime decline. Based on this, the aging resistance performance of different batches can be sensitively differentiated without destructive sampling. This method is also applicable to various aging types, such as thermo-oxidative aging and UV aging, as well as different product forms such as films, fibers, and injection molded parts, demonstrating good versatility.

[0047] In summary, compared with the prior art, the present invention has the following beneficial effects: (1) Stable detection signal and high quantitative accuracy: Using fluorescence lifetime as the detection index, the error caused by light source fluctuation, sample thickness and photobleaching is completely avoided. The detection results of samples with a thickness of 30μm to 480μm have no obvious deviation.

[0048] (2) In-situ detection: Fluorescent probes can be pre-composite inside the material without damaging the sample, and the same sample can be continuously tracked throughout the aging process multiple times.

[0049] (3) Simple operation and high detection efficiency: No complex pretreatment such as solvent dissolution and chromatographic separation is required. A single fluorescence lifetime test only takes a few minutes, which is suitable for rapid screening of batch samples.

[0050] (4) Wide range of applications: It can be adapted to all mainstream polylactic acid product forms such as films, fibers, injection molded parts, 3D printed parts, and coatings. It can accurately quantify both laboratory accelerated aging and outdoor natural aging.

[0051] The above technical features constitute various embodiments of the present invention, which have strong adaptability and implementation effect. Unnecessary technical features can be added or removed according to actual needs to meet the needs of different situations.

Claims

1. A method for detecting the molecular weight of polylactic acid after aging based on changes in fluorescence lifetime using a fluorescent probe, characterized in that... Includes the following steps: Step 1: Composite the fluorescent probe with a polylactic acid substrate to obtain a polylactic acid sample uniformly loaded with the fluorescent probe. Step 2: Aging treatment is performed on the polylactic acid sample to be tested; Step 3: Collect the fluorescence decay curve of the fluorescent probe in the aged polylactic acid test sample to obtain the fluorescence lifetime; Step 4: Substitute the fluorescence lifetime of the aged polylactic acid (PLA) test sample into the pre-established quantitative correlation model between fluorescence lifetime and PLA weight-average molecular weight to calculate the weight-average molecular weight of the aged PLA test sample.

2. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to claim 1, characterized in that... The fluorescent probe is a tetraphenylethylene-based aggregation-induced emission fluorescent probe, wherein the tetraphenylethylene-based aggregation-induced emission fluorescent probe comprises a tetraphenylethylene fluorescent core and oligolactic acid segments covalently grafted onto the tetraphenylethylene fluorescent core; or / and, the mass ratio of the fluorescent probe to the polylactic acid substrate is 0.25:99.75 to 1:

99.

3. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to claim 1 or 2, characterized in that... The composite method is one of physical doping, covalent bonding, or core-shell structure embedding; and / or the aging treatment is one of hydrolytic aging, thermo-oxidative aging, ultraviolet aging, or natural environmental aging.

4. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to claim 2, characterized in that... Tetraphenylyl aggregation-induced emission fluorescent probes are melt-blended with polylactic acid at a temperature of 175°C to 185°C.

5. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to claim 1, characterized in that... The aging process is a hydrolytic aging process, which is carried out in an aqueous solution with a pH value of 4 to 10.

6. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to any one of claims 1 to 5, characterized in that... In step three, the fluorescence decay curve of the fluorescent probe in the aged polylactic acid test sample is collected, including: Fluorescence decay curves were acquired using time-correlated single-photon counting with pulsed laser as the excitation source at wavelengths of 320 nm to 340 nm and fluorescence acquisition wavelengths of 450 nm to 470 nm.

7. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to any one of claims 1 to 6, characterized in that... In step three, the average fluorescence lifetime is the intensity-weighted average fluorescence lifetime, obtained by fitting the fluorescence decay curve using a double exponential function. The calculation formula is as follows: In the formula, τ A1 represents the intensity-weighted average fluorescence lifetime (in ns); A2 and A1 are the pre-exponential factors for short-lived and long-lived fluorescent components, respectively. τ 1. τ 2 represents the fluorescence lifetimes of the short-lifetime and long-lifetime components, respectively.

8. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to any one of claims 1 to 7, characterized in that... Step four: Establish a quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight, including: Multiple sets of polylactic acid standard samples loaded with fluorescent probes were prepared and subjected to aging treatment for different durations to obtain multiple sets of aged polylactic acid standard samples. The average fluorescence lifetime of polylactic acid standard samples after aging treatment was determined. The weight-average molecular weight of polylactic acid standard samples after aging treatment in each group was determined by gel permeation chromatography. A quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight was established by linear fitting with the logarithm of weight-average molecular weight as the ordinate and the average fluorescence lifetime as the abscissa.

9. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to claim 8, characterized in that... The quantitative correlation model between fluorescence lifetime and polylactic acid weight-average molecular weight is expressed as follows: in, Weight-average molecular weight (unit: g / mol). τ The fluorescence lifetime value is expressed in nanoseconds (ns). a and b This is a constant related to the aging path.

10. The method for detecting the molecular weight of polylactic acid after aging based on fluorescence lifetime changes using a fluorescent probe according to claim 2, characterized in that... The tetraphenylethylene-based aggregation-induced emission fluorescent probe was prepared according to the following method: Aminotetraphenylene and L-lactide undergo a polymerization reaction under the action of a catalyst. The reaction product is purified and dried to obtain a tetraphenylethylene-based aggregation-induced emission fluorescent probe. The molar ratio of aminotetraphenylene to L-lactide is 1:1000; The catalyst is stannous octoate; The polymerization reaction is carried out under inert gas protection at a temperature of 110°C to 130°C for 10 to 15 hours.